Identity: "Goat marked for death" - Guerra, Pedro Jorge Coutinho (Seven Editora, 2024)
This work analyzes the problem of peasant identity in Paraíba, from a dialogue with cinematography. The text was anchored both in authors who discuss the theme of peasant identity, as well as in images in visual resources. The complete research is being developed together with the doctoral program in History at the University of Passo Fundo – UPF. DOI:https://doi.org/10.56238/sevened2024.010-046